اعجاز القرآن کا تحقیقی و تجزیاتی مطالعہ: Research and analytical review of I‘jāz-al-Qurān - Rasheed, Majid; Ahmad, Khubaib (Al-Amīr Research Journal for Islamic Studies, 2020)
The Holy Qurān which was revealed to the last Prophet Muhammadﷺ, Just as you are a collection of perfections, so is the word revealed to you a collection of perfections. One of the most important perfections of the Holy Qurān is the miracle of the Holy Qurān. The unique and unique way of reciting the Qurān is called I‘jāz-al-Qurān in Islamic terminology. The Holy Qurān challenged the opponents and deniers of the Holy Qurān to explain its uniqueness.O Beloved! Say: If man and jinn come together and strive to be like the Qurān, they will not be able to make the likeness of it, even if they become helpers of one another. The Qurān is a book of miracles, and miracles are those that are beyond human power and beyond the reach of everyone, power and courage, especially a miracle that lasts for a couple of years or a limited time. Not for the sake of it, but for the challenge of the creation which will come after its coming, and which will make the way of guidance easy for those who ponder within themselves. In this article, I will try to explain the different aspects of I‘jāz-al-Qurān and embellish it with arguments.